1996
DOI: 10.1097/00005537-199609000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Ranvier Node Sodium‐Potassium Adenosine Triphosphatase May Induce Facial Palsy

Abstract: To clarify the part of the neuron essential for myelinated nerve conduction, the cytochemical localization of potassium ion (K+)-dependent p-nitrophenylphosphatase (K-NPPase) activity was investigated in the normal and reserpine-treated facial nerve of guinea pigs. In the normal animals, K-NPPase activity was localized to the internodal axolemma and Schmidt-Lanterman incisures. In the Ranvier nodes, enzyme activity was observed along the paranodal and nodal axolemma. In reserpinized nerves, K-NPPase activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Therefore, two different ouabain-sensitive K-NPPase reactivities, "reserpine-sensitive" and "reserpine-resistant," might be present in the facial nerve. Even when transport Na,KATPase activity on the internodal axolemma was almost completely eliminated, reserpinized animals displayed no facial palsy (Kanoh and Sakagami 1996), and could survive. In 1991, Mata et al reported two different immunoreactivities in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, two different ouabain-sensitive K-NPPase reactivities, "reserpine-sensitive" and "reserpine-resistant," might be present in the facial nerve. Even when transport Na,KATPase activity on the internodal axolemma was almost completely eliminated, reserpinized animals displayed no facial palsy (Kanoh and Sakagami 1996), and could survive. In 1991, Mata et al reported two different immunoreactivities in the nervous system.…”
Section: Discussionmentioning
confidence: 99%